Subjects of Coercion and Persuasion: Patient-Bodies and Kala Azar Preventive Operations in British Assam, 1897–1930 - Bikash Sarma (Social History of Medicine, 2026)
Abstract In the last quarter of the nineteenth century, as the British empire was consolidating itself in the resource-rich North-east frontier of colonial India, it had to grapple with the kala azar epidemics, a disease dreaded for its fatal and contagious character. The complete aetiology of kala azar: its distinction from malaria, the causative organisms and mode of transmission remained a mystery in colonial medicine until the 1940s, and a viable antimony treatment for cure was only available from the 1918 onwards. The epidemiological and economic crisis led an anxious colonial state to carry out a series of preventive measures, and medical and public health interventions targeted at the panic-stricken indigenous bodies to control the spread of the disease. Colonial interventions, coercive at first, were eventually tempered through manipulation and persuasion in line with native temperament and social mores, and to assuage the chequered nature of indigenous responses to it.